Academic history, domains and distribution of the hot-cold system in Mexico - Karina Yaredi García-Hernández; Luis Alberto Vargas-Guadarrama; Heike Vibrans (BMC, 2023)
Abstract Background The hot-cold classification system for things and concepts is widely used by many human groups in Mexico. We conducted a comprehensive review to understand the history, themes, and distribution of this system. Methods We analyzed publications based on field work in Mexico, considering publication date, research approach, study depth, and conceptual domains. We identified the ethnic groups that use the system and the places where they live. A map illustrates the geographic and cultural distribution of the system. Results The hot-cold system has been documented in 101 academic publications spanning almost a century, particularly for traditional medicine and food. Initially dominated by anthropological studies, ethnobotanists have increasingly contributed to the research. The hot-cold system is utilized by at least 56 indigenous ethnic groups (81% of the total) and mestizos (whose primary or sole language is Spanish) across most of Mexico. Discussion Anthropologists laid the foundation for understanding the hot-cold system, on which current ethnobotany builds. However, there are still knowledge gaps, for example on some domains (human beings, landscape) and on patterns by regions or linguistic families. The geographic and cultural distribution presented here is approximate, as group ethnicity is imprecise. Conclusions The hot-cold system is widely applied in Mexico, although some variations exist. Further exploration of understudied domains, and variations between ethnic groups and regions, would contribute to a comprehensive explanation of this interconnected worldview.